The effects of probiotic and phytase on growth performance, biochemical parameters and antioxidant capacity in broiler chickens - Masoud Derakhshan; Seyedeh Ommolbanin Ghasemian; Majid Gholami‐Ahangaran (Veterinary Medicine and Science, 2023)
Abstract Background Probiotics and phytase are commonly used as dietary supplements in poultry diets. Phytase is involved in the release of phosphorus in plant grain ingredient of poultry feed, while probiotics provide beneficial organisms to the gastrointestinal tract. Objective The present study was performed to evaluate the effect of both commercial probiotic and phytase on chicken performance and biochemical indices. Methods A total of 300 chicks were divided into 4 groups that fed the basal diet, diet containing probiotic (Protexin®), Phytase (Meriphyze 5000®), and probiotic plus phytase all over the growing period. The growth indices were measured weekly, analysed at the 21 and 42 days of age. At 42 days of age, blood samples were collected from all chickens. The concentration of liver enzymes, lipid profiles and antioxidant status were measured in blood samples. Results The results showed that the weight gain and feed intake were significantly higher in chickens received phytase alone or phytase in combination with probiotic. The feed conversion ratio (FCR) significantly lower in all supplemented chickens in comparison with control chickens (p < 0.05). Although the addition of probiotic or phytase to chicken diet showed an extent variation in biochemical and antioxidant indices, the addition of phytase plus probiotic showed a significantly increase of blood total protein (TP), albumin (Alb), glutathione peroxidase (GPx), super oxide dismutase (SOD), catalysis (CAT) and total antioxidant capacity (TAC) level, while decrease triglyceride (TG), cholesterol (CHL), aspartate transferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) and malondialdehyde (MDA) in comparison to control chickens. The supplementation of chicken diet with probiotic, phytase or probiotic plus phytase did not effect on low‐density lipoprotein (LDL) and high‐density lipoprotein (HDL). Conclusions The simultaneous supplementation of probiotics and phytases seems to have a positive effect on growth indices in broilers, but they can cause changes in the serum biochemical profile, which sometimes lead to interference and do not always act synergistically.